Endoscopic ultrasound findings and pathological features of pancreatic carcinoma in situ - Izumi, Yoshihiro (Endosc Int Open, 2019)
Background and study aims  Few studies have evaluated detection of pancreatic carcinoma in situ (PCIS). We evaluated findings of endoscopic ultrasound (EUS) and pathological features of PCIS. Patients and methods  We histopathologically studied 16 patients with PCIS following EUS. Diagnostic features evaluated retrospectively included stricture of the main pancreatic duct (MPD) on EUS, presence or absence of hypoechoic areas surrounding the MPD stricture on EUS, the noncancerous part (pancreas of background) on EUS and histopathology, and histological findings adjacent to the area of PCIS. Results  On EUS, stricture of the MPD was found in 15 patients (93.8 %). Hypoechoic areas surrounding the MPD stricture were observed in 9 patients (56.3 %), including three (18.8 %) with a 10- to 11-mm hypoechoic mass. EUS findings of the noncancerous part indicated chronic pancreatitis in six patients (37.5 %), pancreatic fatty infiltration in seven (43.8 %), early chronic pancreatitis in two (12.5 %), and normal pancreas in one (6.3 %). Histological findings of the noncancerous part (proximal to the MPD stricture) indicated chronic pancreatitis in 13 patients (81.3 %) and pancreatic fatty infiltration in five patients (31.3 %). Histopathologically, subepithelial inflammatory cell infiltration and fibrosis were present in all 16 patients with PCIS. Conclusions  PCIS frequently causes localized changes in inflammation and fibrosis around the pancreatic duct. PCIS often accompanies chronic pancreatitis and pancreatic fatty infiltration in the background of the pancreas. EUS offers sufficient resolution to demonstrate pancreatic changes of PCIS.